Hubungan Motivasi terhadap Perilaku Pemberantasan Sarang Nyamuk Demam Berdarah Dengue (DBD) - Yupita Yupita; Melisa Frisilia; Indriani Indriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Dengue hemorrhagic fever (DHF) is one of the public health problems in Indonesia because the number of sufferers and the area of distribution is increasing along with increased mobility and population density. The motivations and behavior of the still diverse people often hinder the PSN movement. In addition, it is also supported by not maximal actions or activities for eradicating mosquito nests (PSN) in the community, causing extraordinary events (KLB). The targets are mosquito breeding places, such as water reservoirs for daily needs or natural water reservoirs or yards. To determine the relationship of motivation to the behavior of eradicating dengue mosquito nests and using the literature review method. The research uses an academic database, namely Google Scholar, published in 2017-2020 using Indonesian and English. Study design Cross-sectional. They obtained six research results according to the inclusion criteria. The research sample is an average of 40-109 respondents. The results of the research analysis showed six research journals that there was a relationship between the factors that influenced the administration of HB-0 immunization in newborns with a value (α = 0.05). There is a relationship between knowledge, family support, occupation, age, education, and motivation in the factors influencing the administration of HB-0 immunization in newborns.